The Construction of Medicolegal Alienation: Physicians’ Lived Experience of Law in Encounters with People Living as Undocumented Migrants in the Context of Medical Humanitarianism - Greenbrook, Josephine T. V.; Reichenberg, Kjell (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2026)
This study introduces medicolegal alienation, a novel form of legal consciousness illuminating physicians’ lived experience of law in engaging in caring for undocumented patients in the context of medical humanitarianism in a welfare state. Empirically grounded findings depict a shifting terrain of medical praxis under restrictive migration regimes and neoliberal health care reforms, illustrating how, by venturing away from the sanctioned territories of conventional medicine, insight into the plight of those confined between legal realms becomes heavily ambiguous. The physician finds themselves liminal by proxy, isolated, marginalized, and overwhelmed by medicolegal alienation as they navigate disrupted care on the thresholds of society.